2019
DOI: 10.1101/738534
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural complementarity facilitates E7820-mediated degradation of RBM39 by DCAF15

Abstract: The investigational drugs E7820, indisulam and tasisulam (aryl-sulfonamides) 13 promote the degradation of the splicing factor RBM39 in a proteasome-dependent mechanism. 14 While the activity critically depends on the Cullin RING ligase substrate receptor DCAF15, the 15 molecular details remain elusive. Here we present the cryo-EM structure of the DDB1-DCAF15-16 DDA1 core ligase complex bound to RBM39 and E7820 at 4.4 Å resolution, together with 17 crystal structures of engineered subcomplexes. We show that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Treating this cell line with the ArSulfs showed no degradation of RBM23 in TMT-proteomics and confirmed the DCAF15 dependency ( Figure S1B). In line with recent reports, [15,17] these results suggest that DCAF15/ArSulf/RBM39 (or RBM23) interaction strictly requires the sequence of the RRM2 domain present in RBM39 and RBM23, confirming ArSulfs as highly selective degraders. Consistent with previous observations [23], we also observed reduced protein levels of MCL1 in the leukemia cell line Mv4;11.…”
Section: Assessing Proteome-wide Selectivity Of the Dcaf15/arsulf/rbmsupporting
confidence: 92%
See 1 more Smart Citation
“…Treating this cell line with the ArSulfs showed no degradation of RBM23 in TMT-proteomics and confirmed the DCAF15 dependency ( Figure S1B). In line with recent reports, [15,17] these results suggest that DCAF15/ArSulf/RBM39 (or RBM23) interaction strictly requires the sequence of the RRM2 domain present in RBM39 and RBM23, confirming ArSulfs as highly selective degraders. Consistent with previous observations [23], we also observed reduced protein levels of MCL1 in the leukemia cell line Mv4;11.…”
Section: Assessing Proteome-wide Selectivity Of the Dcaf15/arsulf/rbmsupporting
confidence: 92%
“…[13,14] Several structural studies have since shown that ArSulfs create a new protein-protein interaction by simultaneously binding both DCAF15 and the splicing factor RBM39 ( Figure 1A). [15][16][17] Since DCAF15 is an E3 ligase adaptor protein, this binding makes RBM39 susceptible to ubiquitination and subsequent degradation in a mechanism that is reminiscent of the more established immunomodulatory drugs (IMiDs) thalidomide and lenalidomide. [18,19] The ArSulfs chloroquinoxaline sulfonamide (CQS), tasisulam, and E7820 ( Figure 1B) are structurally related to indisulam and have all been shown to degrade RBM39.…”
Section: Introductionmentioning
confidence: 99%
“…The overall structure of CPSF160-WDR33 is similar to that of the DDB1-DDB2 complex that is important for sensing and repairing DNA damage [70][71][72]. DDB1 can also interact with other proteins using its three β-propeller domains [73][74][75][76][77]. The BPA and BPC domains and the CTD of CPSF160 are involved in many interactions in the structures determined so far.…”
Section: Cpsf160-wdr33 Is the Core Of The Canonical Machinerymentioning
confidence: 89%
“…In 2019, three independent groups released cocrystal structures of CAPERα–sulfonamide–DCAF15–DDB1–DDA1 multimeric complexes and confirmed that sulfonamides induce formation of the complexes as a molecular glue. 7375 Their structural information could help to further optimize sulfonamides using structure-based drug design and leverage them as DCAF15 ligands for PROTAC design. Until recently, however, it has remained challenging to develop indisulam-based DCAF15-recruiting PROTACs, 76,77 most likely because of the weak binding affinities of these compounds to DCAF15 alone, or perhaps due to unsuitable orientation between the binding pocket of sulfonamides and the RING domain of CUL4.…”
Section: Introductionmentioning
confidence: 99%